1979
DOI: 10.1073/pnas.76.3.1279
|View full text |Cite
|
Sign up to set email alerts
|

Dual control of cell growth by somatomedins and platelet-derived growth factor.

Abstract: Quiescent BALB/c 3T3 cells exposed briefly to a platelet-derived growth factor (PDGF) become "competent" to replicate their DNA but do not "progress" into S phase unless incubated with growth factors contained in platelet-poor plasma. Plasma from hypophysectomized rats is deficient in progression activity; it does not stimulate PDGF-treated competent cells to synthesize DNA. Addition of somatomedin C to hypophysectomized rat plasma stimulates competent cells to synthesize DNA, demonstrating that somatomedin C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
396
1
7

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 835 publications
(420 citation statements)
references
References 40 publications
16
396
1
7
Order By: Relevance
“…Using subsaturating concentrations of growth factors, Pledger, Stiles, Antoniades, and Sher demonstrated that in Balb/c 3T3s cell cycle progression required the input of two di erent types of factors (Pledger et al, 1977(Pledger et al, , 1978Stiles et al, 1979b). Growth factors such as PDGF or FGF made the cells competent, but did not drive them into S phase.…”
Section: Revisiting Competence and Progressionmentioning
confidence: 99%
“…Using subsaturating concentrations of growth factors, Pledger, Stiles, Antoniades, and Sher demonstrated that in Balb/c 3T3s cell cycle progression required the input of two di erent types of factors (Pledger et al, 1977(Pledger et al, , 1978Stiles et al, 1979b). Growth factors such as PDGF or FGF made the cells competent, but did not drive them into S phase.…”
Section: Revisiting Competence and Progressionmentioning
confidence: 99%
“…There is ample evidence indicating that two sets of growth factors, namely 'competence factors' and 'progression factors', successively and synergistically promote the proliferation of cells [16]. In the case of fibroblasts, platelet-derived growth factor and fibroblast growth factor that process cells from Go to G~ phase, belong to the competence factors, whereas insulin, epidermal growth factor and IGF-I that induce progression of cells from G~ to S phase, belong to the progression factors [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the hepatotrophic factors would cause the receptor-mediated hydrolysis of inositol phospholipids, resulting in activation of PKC. Vasopressin, angiotensin and epinephrine, defined as competence factors for cellular growth [15], may activate PKC, and then the activated PKC may mediate the sequence of early events in cellular proliferation of the liver, as speculated for various tissues and cell lines [6,16-2 11. In addition, the activated PKC modulates binding and the phosphorylation of receptors for EGF [22,23], which is defined as a progression factor [15].…”
Section: Immunohistochemical Detection Of Pkc and Dna Replicationmentioning
confidence: 99%
“…Vasopressin, angiotensin and epinephrine, defined as competence factors for cellular growth [15], may activate PKC, and then the activated PKC may mediate the sequence of early events in cellular proliferation of the liver, as speculated for various tissues and cell lines [6,16-2 11. In addition, the activated PKC modulates binding and the phosphorylation of receptors for EGF [22,23], which is defined as a progression factor [15]. The modulation of the EGF receptor by PKC may provide a mechanism whereby competence factor(s) and progression factor(s) can act sequentially in stimulating cell growth.…”
Section: Immunohistochemical Detection Of Pkc and Dna Replicationmentioning
confidence: 99%